An Important Component of Audi's Classical Music - Waniss, Adil Mousa Younis; Balkash, Abdulmajied Ali (Journal of Social Science and Humanities, 2025)
Udra, Kalinga, and Utkal, also known as Odisha, are places of pilgrimage for Lord Jagannath and are renowned for their excellence in arts, music, and culture. Odissi dance and music have flourished in the fertile land of Odisha, a region rich in musical tradition. Odissi Music is known for its subtleness. It is characterized and distinguishable by the elements of spontaneous creativity and embellishment of melody and rhythm with a vibrated movement. The body of an Odissi song is text, while the soul is mood. In Odissi music, there are several types of Prabandhas according to musical and lyrical aspects. Further division has been made to guide performances. The medium pace of singing is what makes its rendering style unique. The Odissiprabandhas are Raganga, Bhabanga, Dhrubapadanga, Natyanga, Champu, Chanda, Chaustisha, Bhajan, Janana, Pallavi and Geetgovind. My focus in this paper will be on the unique chapter of Odissi classical music known as "Champu".